Pengolahan Limbah Cair Tempe Menggunakan Teknologi Hybrid Anoxic Reactor-Sequencing Batch Reactor - Hidayatullah, Naura; Novirina Hendrasarie (Jurnal Serambi Engineering, 2025)
Tempeh wastewater with high organic content requires special treatment to meet environmental standards. This waste has a concentration of BOD5 13,000 mg/L, COD 16,000 mg/L, and Total Nitrogen 2,800 mg/L, far exceeding the quality standards. This study aims to determine the effectiveness of Sequencing Batch Reactor (SBR) in removing pollutants in tempeh liquid waste by adding Anoxic Reactor as pre-treatment and Settling Tank as post-treatment. Variations of HRT, aeration discharge, and settling time were tested to optimize system performance. The results showed that Anoxic Reactor pre-treatment increased Total Nitrogen removal up to 45% at HRT 12 hours. In the SBR unit, optimal conditions occurred at a HRT of 32 hours with an aeration discharge of 14 L/min, resulting in removal of 84% BOD5, 98% COD, and 96% Total Nitrogen. Post-treatment of the settling basin increased the efficiency to 91% BOD5, 87% COD, and 85% Total Nitrogen. The combination of Anoxic Reactor, SBR, and Settling Basin proved to be more effective than without pre-treatment, with the final effluent meeting the quality standards of PermenLHK Number 5 of 2014 and PP Number 22 of 2021, namely: BOD5 133 mg/L, COD 160 mg/L, and Total Nitrogen 21 mg/L.